NAVIGATING NEW WORLDS: THE USE OF MOBILE TECHNOLOGY FOR PSYCHOLOGICAL ADAPTATION AND IDENTITY NEGOTIATION AMONG ASYLUM SEEKER - Nur Hasan; Oumar Traore; Aissatou Coulibaly (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Asylum seekers experience high levels of acculturative stress and identity disruption during the initial settlement phase, often overwhelming traditional, formal support systems. This research aimed to systematically investigate the dynamic role of mobile technology as a self-directed psychosocial resource that mediates psychological adaptation and facilitates identity negotiation. A quantitative, longitudinal study tracked 80 asylum seekers over a six-month period, utilizing Structural Equation Modeling (SEM) to analyze digital trace data collected via the custom Digital Identity and Adaptation Index (DIAAI), alongside validated psychological scales (ASAS, COPE). Results confirmed a strong inverse relationship (beta = -0.45) between Host-Country Media Consumption and Acculturative Stress, validating information seeking as a primary coping mechanism. Furthermore, the findings demonstrated a successful pattern of bi-cultural identity negotiation, where active digital engagement with both the origin and host cultures simultaneously facilitated stress reduction and preserved cultural integrity. The study concludes that the mobile device is a crucial self-directed psychosocial resilience tool, challenging linear models of acculturation. This evidence-based framework justifies the integration of targeted mobile applications into humanitarian aid programs to enhance long-term psychological and integration outcomes.